A study on the influence of media and subject learned in school towards patriotism among youth: a case study in UiTM Merbok, Kedah / Rafidah Razak and Nor Azura Abdul Latif - Razak, Rafidah; Abdul Latif, Nor Azura (2012)
Patriotism can be defined as love of country and willingness to sacrifice for it. The numbers who are showing their patriotic spirit is less as compared to previous year as well as the level of patriotism among Malaysian youths was not as high as expected. The objective of this study is to determine the main factor of patriotism as well as to know the relationship between individualism, history education and global culture influences with patriotism among youth. This study will be focus to UiTM Merbok student as the respondent with aim to understand well about patriotism that possesses especially among youth in UiTM Merbok. The researcher is collecting the data through distributing the questionnaire to the student and analyzes it by using Statistical Package for the Social Sciences SPSS version 16.0.